2015
DOI: 10.1039/c5nr02078f
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-free Gd3+-ion-containing carbon nanotube MRI contrast agents for stem cell labeling

Abstract: There is an ever increasing interest in developing new stem cell therapies. However, imaging and tracking stem cells in vivo after transplantation remains a serious challenge. In this work, we report new, functionalized and high-performance Gd(3+)-ion-containing ultra-short carbon nanotube (US-tube) MRI contrast agent (CA) materials which are highly-water-dispersible (ca. 35 mg ml(-1)) without the need of a surfactant. The new materials have extremely high T1-weighted relaxivities of 90 (mM s)(-1) per Gd(3+) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Both N and q values of the dense Gd 3+ ion cluster are higher than the respective values of the ultrasmall Gd 2 O 3 nanoparticle: q of the Gd 3+ ion in the dense Gd 3+ ion cluster is similar to that of the free Gd 3+ ion and thus higher than that of the nanoparticle, and N of the Gd 3+ ion cluster is also higher than that of the nanoparticle because all the Gd 3+ ions in the Gd 3+ ion clusters can contribute to inducing the longitudinal water proton relaxation whereas in nanoparticles, only the Gd 3+ ions exposed on the nanoparticle surface dominantly contribute to the induction. This explains r 1 values of 70-173 s À1 mM À1 of the dense Gd 3+ ion clusters prepared inside and outside CNTs, [24][25][26] which were 2 to 6 times higher than that of the ultrasmall Gd 2 O 3 nanoparticle in this study. In this way, all the experimental observations of r 1 (Gd 3+ ion cluster) > r 1 (ultrasmall Gd 2 O 3 nanoparticle) > r 1 (free Gd 3+ ) > r 1 (Gd 3+chelate) can be explained using this simple model.…”
Section: Cooperative Induction Model For the Observed High R 1 Valuementioning
confidence: 46%
See 2 more Smart Citations
“…Both N and q values of the dense Gd 3+ ion cluster are higher than the respective values of the ultrasmall Gd 2 O 3 nanoparticle: q of the Gd 3+ ion in the dense Gd 3+ ion cluster is similar to that of the free Gd 3+ ion and thus higher than that of the nanoparticle, and N of the Gd 3+ ion cluster is also higher than that of the nanoparticle because all the Gd 3+ ions in the Gd 3+ ion clusters can contribute to inducing the longitudinal water proton relaxation whereas in nanoparticles, only the Gd 3+ ions exposed on the nanoparticle surface dominantly contribute to the induction. This explains r 1 values of 70-173 s À1 mM À1 of the dense Gd 3+ ion clusters prepared inside and outside CNTs, [24][25][26] which were 2 to 6 times higher than that of the ultrasmall Gd 2 O 3 nanoparticle in this study. In this way, all the experimental observations of r 1 (Gd 3+ ion cluster) > r 1 (ultrasmall Gd 2 O 3 nanoparticle) > r 1 (free Gd 3+ ) > r 1 (Gd 3+chelate) can be explained using this simple model.…”
Section: Cooperative Induction Model For the Observed High R 1 Valuementioning
confidence: 46%
“…Theory of water proton relaxation is very complex. 4,5,38 To understand high r 1 values observed in this study and in various Gd-nanosystems, 14,[24][25][26] however, a simple cooperative induction model was empirically proposed here. In this model, several Gd 3+ ions on the nanoparticle surface or in the dense Gd 3+ ion cluster cooperatively induce the longitudinal water proton relaxation of a water molecule.…”
Section: Cooperative Induction Model For the Observed High R 1 Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the subcellular internalization, Avti et al and Marangon et al observed that gadonanotubes tended to be compartmentalized within endosomes in the cytoplasm of NIH/3T3 cells and RAW 264.7 mouse macrophages, suggesting an active process of cellular internalization. Nevertheless, Hassan et al, Tran et al and Gizzatov et al reported the formation of gadonanotube aggregates in the cytoplasm, but without encapsulation in vesicles (endosomes). Recently, Holt et al used resonant Raman imaging to determine the subcellular distribution of gadonanotubes, finding them predominantly in a perinuclear location of the cytoplasm (Figure ) and that dispersal agents affected the degree of agglomeration.…”
Section: Potential Advantagesmentioning
confidence: 99%
“…[14][15][16] Many different nanoparticles are being explored for such application, however, the special interest in CNTs is based on their high aspect ratio, biocompatibility, [17][18][19] and the capability to be chemically functionalized, [20][21][22][23] while remaining relatively inert. 16 CNTs have been previously used as CAs for different clinical imaging modalities 24,25 such as magnetic resonance (MR), [26][27][28][29][30] ultrasound, 31,32 fluorescence imaging in the near infrared (NIR) region, [33][34][35] Raman scattering, 36,37 photoacoustic, 31,[38][39][40] thermoacoustic, 31,41 CT 42,43 , positron emission tomography (PET), 44,45 and single-photon emission computed tomography (SPECT) imaging. 46,47 In previous work, Wilson and coworkers reported the first CNT-based CA material for X-ray CT imaging that contained Bi 3+ ions within the cavities of ultra-short SWCNTs (US-tubes).…”
Section: Introductionmentioning
confidence: 99%